MULTIPLE DESPROUTING OF SEED TUBERS AND ITS EFFECT ON POTATO PRODUCTION AND PRODUCTIVITY IN HILLY REGIONS - Singh, Sarjeet; Sharma, Ashwani Kumar (Potato Journal, 2013)
Reduction in seed cost of potato by increasing the number of tubers per unit weight was tried through multiple desprouting of seed tubers of potato variety Kufri Jyoti in north-western hills. More than 1cm long sprouts were removed manually and up to a maximum of 4 desproutings were performed sequentially starting from 5 May to 4 July. The results revealed that, only two desproutings when started either on 5 or 20 May were beneficial over control and others. The differences in number of total tubers as well as total yields in first three desproutings started on 5 May were non- significant. However, first two desproutings started on 20 May were better than any other desproutings. Desprouting started on 20 May was better than that of 5 May with 5.4-18.5 and 36.9-43.1 percent increase in number and yield of tubers, respectively.